Effects of school malt drink ingestion pre-exercise on exercise performance in young males - Yong, Keu Sin (Pusat Pengajian Sains Kesihatan, Univerisiti Sains Malaysia, 2013)
INTRODUCTION: Chocolate malt drink which contains carbohydrate is believed able to enhance exercise performance. The purpose of this study was to investigate the effects of chocolate malt drink (CMD) ingestion pre-exercise on exercise performance compared to sports drink (SPD) and plain water (PW) in physically active young males. METHODOLOGY: Twenty male subjects with age between 19 to 25 years old were recruited in this study. Each subjects were required to undergo three randomized cross over 2.4 km running trials with three different test drinks (Chocolate malt drink, sports drink or plain water) on three different days, with one week apart. The subjects were required to refrain from any strenous exercise for 24 hours. There were also required to fast (water intake was permitted) for 8 hours prior to the running trial. In addition, the subjects were required to record the daily dietary intake 3 days before the 2.4 km run for the first trial. After that, the subjects were asked to follow the daily dietary intake as in the first trial 3 days before the second and the third trial. On the test day, subjects were asked to ingest the test drink (300 ml) 15 minutes pre-exercise. After the test drink ingestion, they were required to answer the fluid sensation scale. Subjects were advised to run as fast as possible to achieve the best timing in each trial. Subjects’ post-exercise heart rate, BORG’s scale, rate of perceived exertion (RPE) and fluid sensation scale were recorded at the end of the running trials.RESULT: The result revealed that there were no significant (p>0.05) difference in running time performance between all the three test drinks. The running time in each test drink was SPD (11.33 ± 1.15 min), PW (11.44 ±1.15 min) and CMD (11.59 ± 1.34 min). Besides that, there were no significant (p>0.05) difference in post-exercise heart rate and rate of exertion between all the three test drinks. In term of fluid sensation scale. there were significant (p<0.05) higher value on thirst, nausea and stomach upset significant (p>0.05) difference in fullness sensation in post-exercise compared to preexercise in all the three test drinks. There were significantly higher values (p<0.05) of sweetness sensation in both Cmd and Spd compared to Pw in pre-exercise. CONCLUSION: The results revealed that pre-exercise Cmd ingestion produced almost the similar effects than that in Spd and Pw in term of running time, post-exercise heart rate and rate of perceived exertion. Meanwhile slight higher value of thirsty, nausea and stomach upset sensations were observed following exercise with Cmd, Spd and Pw.